Mesoporous Silica Nanoparticles for Protein Protection and Delivery - Xu, Chun; Lei, Chang; Yu, Chengzhong (Frontiers in Chemistry, 2019)
Therapeutic proteins are widely used in clinic for numerous therapies such as cancer therapy, immune therapy, diabetes management and infectious diseases control. The low stability and large size of proteins generally compromise their therapeutic effects. Thus, it is a big challenge to deliver active forms of proteins into targeted place in a controlled manner. Nanoparticle based delivery systems offer a promising method to address the challenges. In particular, mesoporous silica nanoparticles (MSNs) are of special interest for protein delivery due to their excellent biocompatibility, high stability, rigid framework, well-defined pore structure, easily controllable morphology and tuneable surface chemistry. Therefore, enhanced stability, improved activity, responsive release and intracellular delivery of proteins have been achieved using MSNs as delivery vehicles. Here, we systematically review the effects of various structural parameters of MSNs on protein loading, protection and delivery performance. We also highlight the status of the most recent progress using MSNs for intracellular delivery, extracellular delivery, antibacterial proteins delivery, enzyme mobilization and catalysis.